Peran Desain Inovatif Dalam Mendukung Desa Kreatif (Studi Kasus Desa Pereng Kecamatan Mojogedang Kabupaten Karanganyar) - Rahmanu Widayat; Shafira Hilda Amalia; If Bambang Sulistyono; Desy Nurcahyanti; Deny Tri Ardianto5 (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Pereng Village has declared itself as a creative village since 2023. The village, which is part of Mojogedang District, Karanganyar Regency, besides being an agricultural village, also has potential that can be developed to accelerate the realization of a creative village. However, innovative design touches have not been optimally applied in its arts, culture, and economic and business activities. The questions are: 1) What potentials are there to support a creative village? 2) Why is the image of a creative village important? 3) How can innovative design play a role in supporting the realization of a creative village? This problem was examined through qualitative research with a design theory paradigm with a contemporary interpretation. The results and discussion are that Pereng Village has potential in the agricultural sector in the form of straw waste processed into paper. It has great potential in the arts and culture sector in the form of Reog performing arts, shadow puppet production by local craftsmen, and the formation of a gamelan community. Pereng Creative Village has superior products that, if developed, can benefit the village's economic growth. Innovative design can be aligned in the context of packaging and marketing superior products that are acceptable to today's consumer tastes. The conclusion is that all potential development in Pereng Village requires support until it becomes self-sufficient. Suggestions are needed for government and private sector funding to realize this independent, creative village